Reducing heterotic M-theory to five dimensional supergravity on a manifold with boundary - Moss, Ian G.; Omotani, John T.; Saffin, Paul M. (Springer Verlag, 2011)
This paper constructs the reduction of heterotic M-theory in eleven dimensions to a supergravity model on a manifold with boundary in five dimensions using a Calabi-Yau three-fold. New results are presented for the boundary terms in the action and for the boundary conditions on the bulk fields. Some general features of dualisation on a manifold with boundary are used to explain the origin of some topological terms in the action. The effect of gaugino condensation on the fermion boundary conditions leads to a `twist' in the chirality of the gravitino which can provide an uplifting mechanism in the vacuum energy to cancel the cosmological constant after moduli stabilisation.